Implementasi Lean Canvas Pada Startup Dalam Menghadapi Persaingan Bisnis Barbershop - Tuti Wediawati; Ella Fitria Rahmayani (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study is, namely to describe the use of lean canvas at startup using the components contained in it,to explain the factors considered by managers in implementing lean canvas, to identify the constraints contained in implementing lean canvas, and the benefits associated with it. It can be in the application of lean canvas. This research is a descriptive study with a qualitative approach. The authors conducted interviews and observations in collecting data. The result of this research is the application of lean canvas to the Toekang Coekoer business model, so that it can be make it easier to determine the strategy in its development